In situ 형성이 가능한 헤파린과 PEG계 생체 적합성 하이드로젤 - You, Seung Soo (The Graduate School, Ajou University, 2011)
Surface modification of the biomaterials was widely investigated to improve bio compatibility. In particular, the PEG based hydrogel coating systems were developed due to various advantages of the hydrogels such as high hydrophilicity and lubricity. Heparin has been studied as a bio-active material for surface modification to produce not only bio compatible surface but also anti-coagulant surface. Heparin is the most commonly used anticoagulant reagent in clinical use and heparinization of surfaces which has been shown to be a successful strategy to prevent thrombus formation and to improve blood compatibility of blood-contacting medical devices. However, physical adsorption of hydrogels limits the durability in the long-term exposure in vivo. In this study, in situ forming heparin and PEG based hydrogels as a coating material was developed to improve blood compatibility of the metal devices and the durability of the hydrogel coating layer on the surface. 316L stainless steel (SS) substrates were simply and rapidly coated with hydrogels via horseradish peroxidase (HRP) enzymatic reaction in presence of hydrogen peroxide (H2O2). After hydrogel coating, durability of the hydrogel coating layer was evaluated. Heparin and PEG based hydrogel coating layer was stable for 7 days. Hydrogel coated surface effectively inhibited the protein adsorption and platelet adhesion. Surface bound heparin has suppressed the coagulation on the hydrogel coated surface by inactivating antithrombin. Our results demonstrated that the in situ forming heparin and PEG based hydrogel has great potential for use as a surface coating materials to improved blood compatibility of the metal surface.
학위논문(석사)--아주대학교 일반대학원 :분자과학기술학과,2011. 2